PENTINGNYA PROMOSI GUNA MENINGKATKAN MINAT WISATAWAN WISATA SEJARAH DI KOTA LAMA SEMARANG - Dewi Hermin Sutanto (Jurnal Pariwisata Pesona, 2016)
The tourism industry has excellent prospects in moving the economy that can reliably increase the revenue of the country, broaden and flatten the opportunity to strive and their new jobs for people, especially stakeholder in tourism. Development of tourism in Indonesia is not separated from the development in each area in Indonesia. One of them is Semarang, Central Java, which has the rich culture and history that can be used as a tourist attractions. One area that is currently being intensively developed, exploring the potential of Semarang, giving the opportunities for tourism businesses for the society in Central Java. The purpose of this research is to determine how far the importene of promotion to increase tourist interest in history tourism at old town Semarang. The result of the questionnaire which addressed to domestic tourist, the writer condude as follows: 1) circumstances and historical tourism potential of old city in Semarang is very attractive for the visitors, but in terms of management and the facilities both of them are need to be improved, 2) Human resources is less skilled and less experienced in tourism so they need to train their skill to participate in developing the potential and visitors attractions. The method used is descriptive method by collecting data and identifity the problems that exist in old town Semarang.